Factors associated with cerebral palsy among children in Hawassa University comprehensive specialized hospital: Case-control study - Bethelhem Bashe; Desalegn Dawit Assele; Worku Ketema; Mulugeta Sitot Shibeshi (PLoS ONE, 2025)
Background Cerebral palsy is a frequent physical disability of childhood, causing motor impairment, sensory impairment, cognitive and behavioral issues, and secondary musculoskeletal deformities, with a global incidence of 1–4 per 1,000 children. It significantly impacts children’s quality of life and imposes an economic burden on families and healthcare systems. There is limited evidence of the risk factors of cerebral palsy in Ethiopia, including in the study setting. We investigated factors associated with cerebral palsy among children attending Hawassa University Comprehensive Specialized Hospital. Methods An institution-based, unmatched case-control study was conducted among children who visited Hawassa University Comprehensive Specialized Hospital from January 2019 to December 2023. Consecutive cases were recruited until the required sample size was reached, and controls were randomly selected. Data were extracted from 80 cases and 160 control charts. Binary logistic regression analysis was used to identify risk factors for cerebral palsy. An adjusted odds ratio with a 95% confidence interval was reported to show the strength of the association. The significance of the association was declared at a p-value < 0.05. The goodness-of-fit model was checked by the Hosmer and Lemeshow test. Results A total of 240 participants (80 cases and 160 controls) were enrolled in the study. Maternal infection during pregnancy [AOR:4.1; 95%; 1.39, 12.1], low birth weight [AOR:4.1; 95%; 1.49, 11.2], prolonged labor [AOR:3.2; 95%;1.47, 7.00], history of perinatal asphyxia [AOR: 2.65; 95%;1.06, 6.65], and central nervous system infection during infancy [AOR:3.4; 95%; 1.21, 9.64] were risk factors for cerebral palsy. Conclusion Perinatal asphyxia, maternal infection, low birth weight, prolonged labor, and CNS infection during infancy are significantly associated with cerebral palsy. Public health education should promote awareness about cerebral palsy, encourage antenatal care, and educate healthcare professionals on emergency obstetrics and newborn care. Appropriate measures should be taken to reduce the incidence of CNS infections during infancy.